2008
DOI: 10.1007/s11154-008-9103-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining human diabetic nephropathy on the molecular level: Integration of transcriptomic profiles with biological knowledge

Abstract: Diabetic nephropathy (DN) is the most common cause for end stage renal disease (ESRD). Next to environmental factors, genetic predispositions determine the susceptibility for DN and its rate of progression to ESRD. With the availability of genome wide expression profiling we have the opportunity to define relevant pathways activated in the individual diabetic patient, integrating both environmental exposure and genetic background. In this review we summarize current understanding of how to link comprehensive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 51 publications
(52 reference statements)
2
57
0
Order By: Relevance
“…3 Furthermore, a recent observational study suggests that inhibition of inflammasome signaling improves renal function (on the basis of a decline in serum creatinine) in patients with established dNP. 18 Likewise, the data obtained from the Nephromine dataset 19 demonstrate that inflammasome, but not apoptosis, regulators are induced in glomeruli of patients with diabetes, which further supports a crucial role of inflammasome activation for dNP, not only in rodents, but also in humans.…”
mentioning
confidence: 63%
“…3 Furthermore, a recent observational study suggests that inhibition of inflammasome signaling improves renal function (on the basis of a decline in serum creatinine) in patients with established dNP. 18 Likewise, the data obtained from the Nephromine dataset 19 demonstrate that inflammasome, but not apoptosis, regulators are induced in glomeruli of patients with diabetes, which further supports a crucial role of inflammasome activation for dNP, not only in rodents, but also in humans.…”
mentioning
confidence: 63%
“…Likewise, glomerular lipid accumulation and mesangial matrix expansion was increased in non-diabetic Lxrα/β −/− mice compared with Lxrα/β +/+ mice. This new model of renal disease may be relevant to human disease, since the expression of LXRα and LXRβ is significantly decreased in patients with DN compared with controls [27] and renal biopsies from patients with DN show lipid deposition primarily in glomeruli [41][42][43]. Recent studies looking at LXR action in the kidney have shown improved albuminuria with other LXR ligands (T091317, GW3965) and different animal models of DN (STZ C57Bl/6, STZ Ldlr −/− ) [28,29]; however, these studies were unable to address the importance of LXR in baseline renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Human biopsies and experimental rodent models have revealed a consistent downregulation of LXRs in DN compared with control [26,27], and experiments with firstgeneration LXR ligands have shown anti-inflammatory and anti-albuminuric actions in diabetic mice [28,29]. While these observations are promising for the development of DN therapies targeting LXRs, several fundamental questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…Unprocessed gene expression datasets are available in the Gene Expression Omnibus and have also been integrated into the renal search engine Nephromine (www.nephromine.org) for additional systems biology analysis by the renal research community. 39 GWAS, intrarenal transcriptional profiles, and biologic knowledge together were able to define a tight pathway-crosstalk activated Figure 4. CKD associated pathways are shared between renal diseases.…”
Section: The Ckd Pathway Network As a Resource For The Renal Researchmentioning
confidence: 99%